Oogenesis at subzero temperatures: a comparative study of the oocyte morphology in nine species of Notothenioides - MOTTA, CHIARA MARIA; CAPRIGLIONE, TERESA; SIMONIELLO, PALMA; TAMMARO, STEFANIA; FILOSA, SILVANA; Frezza V (Tissue and Cell, 2005)
Oogenesis was examined in nine species of Antarctic fish to verify the existence of morphological peculiarities. The analyses were carried out on specimens belonging to three different families of Notothenioids (Nototheniidae, Channichthyidae and Bathydraconidae), all captured in the Ross Sea, in front of the Italian Station of Terra Nova Bay. Following dissection, the ovaries were processed and examined at the light and electron microscopes to determine the oocyte gross and fine morphology. The attention, in particular, was focused on the presence of cytoplasmic round bodies and on the organization of the cortical alveoli and the vitelline envelope. Results reveal significant specie-specific differences that could be partly correlated to the phylogenetic radiation but not to the peculiar environmental conditions being essentially comparable to those observed among temperate species.